Phylogenetic profiling and cellular analyses of ARL16 reveal roles in traffic of IFT140 and INPP5E - Dewees, Skylar I; Vargová, Romana; Hardin, Katherine R; Turn, Rachel E; Devi, Saroja; Linnert, Joshua; Wolfrum, Uwe; Caspary, Tamara; Eliáš, Marek; Kahn, Richard A (Molecular biology of the cell, 2022)
The ARF family of regulatory GTPases is ancient, with 16 members predicted to have been present in the last eukaryotic common ancestor. Our phylogenetic profiling of paralogues in diverse species identified four family members whose presence correlates with that of a cilium/flagellum: ARL3, ARL6, ARL13, and ARL16. No prior evidence links ARL16 to cilia or other cell functions, despite its presence throughout eukaryotes. Deletion of ARL16 in mouse embryonic fibroblasts (MEFs) results in decreased ciliogenesis yet increased ciliary length. We also found Arl16 knockout (KO) in MEFs to alter ciliary protein content, including loss of ARL13B, ARL3, INPP5E, and the IFT-A core component IFT140. Instead, both INPP5E and IFT140 accumulate at the Golgi in Arl16 KO lines, while other intraflagellar transport (IFT) proteins do not, suggesting a specific defect in traffic from Golgi to cilia. We propose that ARL16 regulates a Golgi-cilia traffic pathway and is required specifically in the export of IFT140 and INPP5E from the Golgi.
Keywords: cilie; Animals; fosfatasy; transportní proteiny; transport proteinů; Phylogeny; Carrier Proteins; Protein Transport; Proteins; proteiny; zvířata; Phosphoric Monoester Hydrolases; Mice; Cilia; fylogeneze; fibroblasty; Fibroblasts; myši